Gaining new insights into macroplastic transport 'hotlines' and fine-scale retention-remobilisation using small floating high-resolution satellite drifters in the Chao Phraya River estuary of Bangkok. (1st March 2023) - Mani, Thomas; Hawangchu, Yotwadee; Khamdahsag, Pummarin; Lohwacharin, Jenyuk; Phihusut, Doungkamon; Arsiranant, Isara; Junchompoo, Chalatip; Piemjaiswang, Ratchanon
Abstract: In river plastic pollution research little is known about the detailed pathways and interruptions that occur during the journey of macroplastic debris (>5 cm) from land to sea. Data on fine-scale and high-accuracy transport trajectories and cycles of retention (when macroplastics are trapped, e.g. at a pier) and remobilisation is needed to inform global river plastic transport models as well as mechanical cleanup efforts. Though well established in the marine environment, the use of floating satellite drifters to understand macroplastic debris transport in tidal rivers and estuaries is in its infancy. Exploring the capacity to investigate fine-scale macroplastic debris-estuary interactions, this study brings together, on the one hand, a small, sensitive, floating satellite drifter with, on the other hand, the major riverine-marine habitat of the Chao Phraya River estuary at Bangkok, Thailand. The used grapefruit-sized drifters (n = 5) with minimal drogue (ρ ≈ 0.67 g/cm 3 ) sent their positions at up to 4 m and 5 min spatiotemporal resolution via cellular GSM network for up to 48 days. This study indicates that river macroplastic debris transport 'hotlines' (positions where floating debris will likely pass by in a river) as well as retention-remobilisation cycles can be studied at fine scale. On their way through the river and gulf, covering between 9 and 696 km, drifters got stuck up to 23 times, spending 80% of their river lifetime in retention. Furthermore, it is outlined that the trajectories can be linked with environmental factors such as bathymetry and tides to more accurately model macroplastic debris behaviour in rivers. Finally, it is shown that trajectories crossing the riverine-marine continuum at the estuary can be accurately traced to support future investigations on the so far scarcely evidenced river mouth emissions of macroplastic debris. Graphical abstract: Image 1 Highlights: High-resolution satellite drifters enable investigation of fine-scale spatiotemporal transport of floating debris. Location report resolution of up to 5 min and 4 m provide new insights. The study indicates potential formation of high probability floating debris hotlines.